PENGARUH BEBAN KERJA DAN STRES KERJA TERHADAP BURNOUT PADA SAAT COVID-19 - Afiansyah, Mohamad Rizki; Adi, Agung Nugroho (Jurnal Kewirausahaan dan Inovasi, 2023)
The objectives of this study are to identify the partial effects of workload and job stress on burnout among health workers at the Gambiran Regional Public Hospital of Kediri City and to identify which variable that is more dominant in affecting the burnout. This quantitative study is categorized as explanatory research, in which the hypothesis testing was used to identify the effects of the independent variable, i.e., workload (X1) and job stress (X2), on the dependent variable, i.e., burnout (Y). Using 52 people as the respondents and multiple linear regression for the hypothesis testing, this study finds that workload positively and significantly influences burnout and that job stress does not influence burnout. Furthermore, the variable that has a more dominant impact on burnout (Y) is workload (X1). Therefore, it is suggested that Gambiran Regional Public Hospital of Kediri City pay more attention on the workload of its health workers in order to reduce burnout and to keep the job stress level of its health workers minimum.